Dynamic cognitive inhibition in the context of frustration: Increasing racial representation of adolescent athletes using mobile community-engaged EEG methods - Hudac, Caitlin M.; Wallace, Jessica S.; Ward, Victoria R.; Friedman, Nicole R.; Delfin, Danae; Newman, Sharlene D. (Frontiers in Neurology, 2022)
Introduction Concussive events and other brain injuries are known to reduce cognitive inhibition, a key aspect of cognition that supports ones' behaviors and impacts regulation of mood or affect. Our primary objective is to investigate how induction of negative affect (such as frustration) impacts cognitive inhibition and the dynamic process by which youth athletes modulate responses. Secondary objective is to address the lack of Black representation in the scientific literature that promotes brain health and investigates pediatric sports-related brain injury. In particular, neuroscience studies predominantly include White participants despite broad racial representation in sport, in part due to technological hurdles and other obstacles that challenge research access for Black participants. Methods Using electroencephalography (EEG), we evaluate the dynamic brain processes associated with cognitive inhibition in the context of frustration induction in adolescent athletes during pre-season conditioning (i.e., prior to contact; N = 23) and a subset during post-season (n = 17). Results The N2 component was sensitive to frustration induction (decreased N2 amplitude, slower N2 latency), although effects were less robust at postseason. Trial-by-trial changes indicated a steady decrease of the N2 amplitude during the frustration block during the preseason visit, suggesting that affective interference had a dynamic effect on cognitive inhibition. Lastly, exploratory analyses provide preliminary evidence that frustration induction was less effective for athletes with a previous history of concussion or migraines (trending result) yet more effective for athletes endorsing a history with mental health disorders. Discussion We emphasize the urgent need to improve representation in cognitive neuroscience, particularly as it pertains to brain health. Importantly, we provide detailed guides to our methodological framework and practical suggestions to improve representative participation in studies utilizing high-density mobile EEG.